3D Virtual Patient in Dentistry: A Comprehensive Literature Review - Hanen Boukhris; Ameni Thabet; Asma Ben Dalla; Nouha M’ghirbi; Siham Hajjaji; Hayet Hajjemi; Souha Ben Youssef (Science and Technology - Recent Updates and Future Prospects Vol. 3, 2024)
Aims: This narrative review seeks to delve deeply into the utilization of facial scanning technology in dentistry, specifically focusing on the acquisition of 3D virtual patients. The goal is to examine the development of different kinds of facial scanning technology and their contemporary applications in the field. Methodology: Subcategories within facial scanner technology were delineated, and systematic searches were conducted on the Medline (PubMed) database and Google Scholar in February 2024 to compile relevant literature. The search strategy lasted for three weeks. Twenty-four articles were reviewed, focusing solely on studies and reviews addressing facial scanning in dentistry. Results: The review delves into the historical progression of facial scanning technology, explores the diverse technologies and approaches used in dentistry, evaluates precision in scanning, assesses diagnostic effectiveness, and explores its contributions to generating 3D and 4D virtual patients, virtual occlusion, and smile design within the dental field. Conclusion: Despite challenges in scan accuracy and complexities in file matching, facial scanners offer rapid and accurate solutions for various dental applications. While further advancements are needed to address existing limitations, facial scanning technology shows potential for improving restorative dental treatment planning in the near future.